(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
In this research, health risk assessment due to the emission of pollutants from a medical waste incinerator located within industrial estate in the northern part of Malaysia was presented. The influence of pollutants emission in the vicinity of the incineration plant was the main concern in this research. The measured emissions of pollutants from the stacks of the studied plant that may pose risk to human health and the environment are compared against the acceptable limit as in the Environmental Quality (Clean Air) Regulation 2014. Next, the levels of pollutants in ambient air are assessed in comparison with the guideline established by the Malaysia Ambient Air Quality Guideline (MAAQG). The health risk assessment was then conducted by calculating the quantitative risk for non-carcinogenic and carcinogenic pollutants. The study reveals that the total cancer risk due to emission of carcinogenic pollutants from the incinerator is 1.84 x 10-5, which indicates risky circumstances as the calculated risk is higher than the benchmark of acceptable risk of 1 x10-6. Meanwhile the health risk calculated due to emission of non-carcinogenic pollutants ranges between 0.000286 and 0.1, indicating acceptable risk. The result shows that the non-carcinogenic pollutants emitted from the studied medical waste incinerator are within the acceptable exposure limits. However, for carcinogens, the released amounts may cause human health risk, and therefore demands for further attention to reduce the concentrations as low as reasonably practicable, at least in compliance with the established guidelines.Â